Shallot (Allium cepa L.) Peel Infusion Ameliorates Kidney Histopathological Damages in Diazinon-Induced Wistar Rats - Bi’izzyk, Avie Baldana; Helianti, Dina; Wahyudi, Septa Surya; Dewi, Rosita (Majalah Kedokteran Bandung, 2024)
Diazinon, an organophosphate pesticide, is used extensively in agricultural sector. Consumption of agricultural products containing diazinon residue may lead to harmful health consequences. Among these is nephrotoxicity, which includes lipid peroxidation, that can damage the kidney. Flavonoids in shallot peel can scavenge free radicals, inhibit necrosis, and activate bone marrow-derived cells for cell regeneration. This study aimed to determine the correlation between shallot peel infusion (SPI) dose and kidney damage amelioration to establish the maximum effective dose of SPI to ameliorate kidney histopathological damage in diazinon-induced rats. This study was performed at the Pharmacology Laboratory, Faculty of Medicine, University of Jember, Indonesia, in April 2021, on 35 rats that were divided into 7 groups—normal, diazinon, and five treatment groups. Diazinon 40 mg/kgBW was administered on day 1-7, while SPI 125, 250, 500, 1,000, 2,000 mg/kgBW were administered on day 8–14 according to the treatment group. Kidney histopathological slides with hematoxylin-eosin (H.E.) staining were assessed using Kocoglu scoring and Kidney damage scores of the treatment groups were analyzed using Pearson test. The maximum effective dose was determined using regression test. The damages found in diazinon-induced rats were tubular degeneration, necrosis, and inflammation with a higher damage score than normal rats (p<0.05). Pearson test showed moderate correlation (coefficient -0.594). Higher SPI doses presented lower kidney damage scores, with 1,359 mg/kgBW being the maximum effective dose. SPI dose and the kidney damage amelioration are moderately correlated with a SPI maximum effective dose to ameliorate kidney damage in diazinon-induced rats of 1,359 mg/kgBW.